2016
DOI: 10.4103/2152-7806.188914
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal extradural meningioma: Case report and literature review

Abstract: Background:Extradural spinal mass lesions are most commonly metastatic tumors. Extradural meningiomas are rare, accounting for approximately 2.5–3.5% of spinal meningiomas; intraoperatively, they are easily mistaken for malignant tumors, especially in the en plaque variety, resulting in inadequate surgical treatment.Case Description:Our case is one of the first to describe a patient with two purely extradural meningiomas, one each between D3–D4 and between D5–D6 vertebral levels. Surgical resection was radical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Among the 14 patients with epidural meningiomas in the current study, the male/female ratio was 4:10 and the mean age was 44.9 years; this sex distribution and age are consistent with those in previous reports. 10,17 In terms of tumor location, 12 tumors in this series were in the cervical spinal canal and 2 were in the thoracic spinal canal. This location is contrary to the findings of Frank et al, 18 who reported that the thoracic spine is the typical location of epidural meningioma.…”
Section: Discussionmentioning
confidence: 94%
“…Among the 14 patients with epidural meningiomas in the current study, the male/female ratio was 4:10 and the mean age was 44.9 years; this sex distribution and age are consistent with those in previous reports. 10,17 In terms of tumor location, 12 tumors in this series were in the cervical spinal canal and 2 were in the thoracic spinal canal. This location is contrary to the findings of Frank et al, 18 who reported that the thoracic spine is the typical location of epidural meningioma.…”
Section: Discussionmentioning
confidence: 94%
“…Most patients present with pain (57%), motor deficits (57%), and sensory deficits (50%), typically over an average of 19 months. [ 2 - 5 ]…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…MRI is the modality of choice for the diagnosis of spinal meningioma because it clearly defines the mass and its relation to the spinal cord. Mostly, the lesion shows iso to hypointensity on T1-weighted images, variable signal intensity on T2-weighted images, with homogeneous enhancement after Gadolinium injection (1,6). Epidural meningiomas may be en plaque, dumbbell-shaped, or fusiform/ovoid (1).…”
Section: Discussionmentioning
confidence: 99%